Characterization and Developmental Expression Patterns of Four Hexamerin Genes in the Bumble Bee, Bombus terrestris (Hymenoptera: Apidae). Issue 5 (12th October 2021) - Tian, Yakai; Qu, Yingping; Dong, Kun; He, Shaoyu; Jie, Wu; Huang, Jiaxing
Abstract: Hexamerins are members of the hemocyanin superfamily and play essential roles in providing amino acids and energy for the nonfeeding stages of insects. In this study, we cloned and analyzed the expression patterns of four hexamerin genes ( hex 70a, hex 70b, hex 70c, and hex 110 ) at different worker development stages and queen diapause statuses in the bumble bee, Bombus terrestris . The results of this study showed that hex 110 has the longest open reading frame (ORF; 3, 297 bp) compared to the ORFs of hex 70a (2, 034 bp), hex 70b (2, 067 bp), and hex 70c (2, 055 bp). The putative translation product of Hex 70a, Hex 70b, Hex70c, and Hex 110 has 677, 688, 684, and 1, 098aa with predicted molecular mass of 81.13, 79.69, 81.58, and 119 kDa. In the development stages of workers, the expression levels of hex 70a, hex 70b, and hex 70c increased gradually from the larval stage and exhibited high expression levels at the pink eyed and brown eyed pupae stage, whereas hex 110 exhibited the highest expression level at the larval period. Four hexamerin genes were highly expressed at the prediapause status of queen ( P < 0.05), and compared to the eclosion queen, the lowest upregulation was 3.7-fold, and the highest upregulation was 1, 742-fold. The expression levels of hex 70b, hex 70c, and hex 110 at diapause were significantly higher than those at postdiapause ( P < 0.05). In conclusion, hexamerins may play important roles in queen diapause and metamorphosis of larval and pupal stages.